Chemically conjugated sophorolipids on CdTe QDs: a biocompatible photoluminescence nanocomposite for theranostic applications - Singh, Pooja; Joshi, Kasturi; Guin, Debanjan; Prabhune, Asmita (RSC Advances, 2013)
Functional nontoxic cadmium telluride (CdTe) quantum dots (QDs) have been synthesized using a natural functional glycolipid belonging to the family of sophorolipids (SL) as a surface-modifying agent. These SLs with open acidic form are highly suitable for QDs stabilization, are readily obtained by a fermentation process of the yeast Candida bombicola (polymorph Starmerella bombicola) in large amounts. In this work chemically stable, water soluble, and photoluminescent CdTe QDs were successfully conjugated to sophorolipids via a cross-linking reaction. The formation of SLs conjugated CdTe QDs was confirmed using different analytical techniques X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Electron Diffraction (ED), Atomic Force Microscopy (AFM), Dynamic Light Scattering (DLS), and Photoluminescence (PL). It was shown that after being conjugated with SL the SL-CdTe QDs becomes biocompatible, still maintaining its water solubility and photoluminescence properties. The final SL coated photoluminescent CdTe QDs represent interesting biocompatible materials potentially useful for biomedical applications.

Glucose oxidase conjugated H2O2 sensitive CdTe QDs: an effective fluorescence tool for glucose sensing - Singh, Pooja; Prabhune, Asmita; Ogale, Satishchandra B.; Guin, Debanjan (Journal of Materials Chemistry B, 2013)
Water-soluble quantum dots (QDs) are extensively used for molecular sensing because of the flexibility they offer in terms of modification of the QDs surface with a variety of functional groups using thiol chemistry and monitoring by fluorescence intensity. We describe a simple assay that allows the photoluminescence (PL) detection of H2O2 and glucose in aqueous samples and demonstrate its applicability by estimating glucose in blood. To enable the glucose detection, we functionalized the 3-mercaptopropanoic acid (MPA) capped CdTe QDs with glucose oxidase (GOx), the enzyme specific to b-D-glucose, using carbodiimide chemistry. The fluorescence of the GOx-functionalized CdTe QDs was quenched on the interaction with glucose. The same photoluminescence quenching was also observed in gel form, when a GOx modified CdTe QDs loaded agarose gel was dipped in H2O2 and glucose solutions, respectively.

Blue luminescent graphene quantum dots by photochemical stitching of small aromatic molecules: fluorescent nanoprobes in cellular imaging - Gokhale, Rohan; Singh, Pooja (Particle & Particle Systems Characterization, 2014)
Blue fluorescent graphene quantum dots (GQDs) are synthesized from small haloaromatic molecules by laser photochemistry. The process involves a bottom-up photochemical stitching mechanism of the free radicals generated by irradiation of ultraviolet photons (lambda = 248 nm) on o-dichlorobenzene. The GQDs are further demonstrated to be of importance as fluorescent nanoprobes in bioimaging of cells.image
Keywords: bioimaging; free radicals; graphene quantum dots; photochemical stitching; UV laser